Assessing the quality of Selangor Islamic Religion Council (MAIS) website: a descriptive study - Ab Hamid, Ahmad Rauyani (2020)
MAIS is the main authority of religious affairs in Selangor. Its website has served an important platform for the state government to communicate with the public matters related to Islam. However, little research was done on the quality of this website. This study used quantitative approach method. Three experienced ICT lecturers were purposively selected to rate the website using Chua, Goh and Ang’s web quality indices. Out of 15, the overall quality of the MAIS website is in the range of 9.75 to 12.75. The three dimensions of web quality indices were viewed favourably. However, there is a need to improve on the aesthetic aspect of the website.